A Mild and Base-Free Synthesis of Unsymmetrical Diaryl Sulfones from Arylboronic Acids and Arylsulfonyl Hydrazides - Wu, Xiang-mei; Wang, Yan (Synlett, 2014)
A mild and efficient synthesis of diaryl sulfones from arylboronic acids and arylsulfonyl hydrazides is described. Promoted by cupric acetate and in the absence of additional ligand and base, the cross-coupling reaction could afford a series of unsymmetrical diaryl sulfones in moderate to good yields at room temperature under neutral and ambient conditions.
Keywords: diaryl sulfone; arylboronic acid; arylsulfonyl hydrazide; cross-coupling reaction; copper